Enzymatic hydrolysis of sorghum bagasse to readily fermentable sugar for bioethanol - Soeprijanto Soeprijanto; Katherin Indriawati; Nurlita Abdulgani (Jurnal Rekayasa Proses, 2014)
Production of sugar from sorghum bagasse using enzyme of cellulase and cellobiase in a batch culture was conducted. The purpose of this experiment was to study of the effect of sorghum baggase loadings and lime pretreatment time on production and yield of sugar. Lime pretreatment was carried out in a 1000 ml three-neck flask with a lime loading of 0.1 g Ca(OH)2 /g sorghum bagasse and added with 500 ml distilled water. Effects of pretreatment time course (1, 2, 3, and 4 h) at temperature of 100°C and biomass loading (5, 10, 15 % w/v) were observed to produce sugar. The results showed that maximum concentration of sugar obtained was 28.04 g/l with a pretreatment time of 4 h; and the maximum yield of sugar obtained was 0.4 g glucose/ g biomass with a biomass loading of 5% (w/v).